2010
DOI: 10.1128/jcm.01671-09
|View full text |Cite
|
Sign up to set email alerts
|

Application of Truncated Immunodominant Polypeptide from Hepatitis E Virus (HEV) ORF2 in an Assay To Exclude Nonspecific Binding in Detecting Anti-HEV Immunoglobulin M

Abstract: The diagnosis of recent hepatitis E virus (HEV) infection depends on serologic testing for anti-HEV IgM; however, false-positive results may occur. In the present study, we cloned the ORF2 fragment of genotype 4 HEV and demonstrated that a subregion covering amino acids 459 to 607 in ORF2 forms the immunodominant B-cell epitopes, as it does in genotype 1 viruses. Truncation of several residues from either the N or C terminus of the polypeptide abolished the reactivity of anti-HEV from naturally infected person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
(43 reference statements)
0
13
0
Order By: Relevance
“…Several studies have emphasized the unsatisfactory performance of anti‐HEV assays [30–40]. In this study, the performance of assays for the detection of anti‐HEV IgM and IgG from three manufacturers, Mikrogen (IgM and IgG assays), MP Biomedicals (IgM assay only) and Fortress Diagnostics (WanTai IgM and IgG assays), was compared.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have emphasized the unsatisfactory performance of anti‐HEV assays [30–40]. In this study, the performance of assays for the detection of anti‐HEV IgM and IgG from three manufacturers, Mikrogen (IgM and IgG assays), MP Biomedicals (IgM assay only) and Fortress Diagnostics (WanTai IgM and IgG assays), was compared.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the performance of assays for the detection of anti‐HEV IgM and IgG from three manufacturers, Mikrogen (IgM and IgG assays), MP Biomedicals (IgM assay only) and Fortress Diagnostics (WanTai IgM and IgG assays), was compared. Previous studies reported better sensitivity of the WanTai assays (Fortress Diagnostics) compared to other assays [36,37,40], but these had not been compared to the recom Well assays (Mikrogen) that differ from most other commercially available assays by utilizing capture antigens from both genotype 1 and genotype 3. Considering that no data were available regarding the HEV strains circulating in Ghana, the recom Well assays were favoured for this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in most assays, the antigens used for antibody capture are derived from HEV genotype 1 or genotypes 1 and 2. Because the HEV genotypes thus far identified to infect animals belong instead to genotype 3, genotype 4, and the newer putative genotypes, the possibility that low antibody detection rates reflect weak binding of antibody to heterotypic antigens rather than true antibody absence (2,19,24,44,45,48,62) cannot be excluded.…”
mentioning
confidence: 99%
“…ORF2 is located at the 3' end of the genome and encodes a capsid protein that encapsulates the viral RNA genome and contains an endoplasmic reticulum (ER) signal peptide and 3 putative N-glycosylation sites (Graff et al, 2008), which have been the focus of studies of antigenic sites (Ma et al, 2009;Pan et al, 2010). However, recent studies compared the polypeptide ends of the ORF1, ORF2 and ORF3 proteins.…”
Section: Discussionmentioning
confidence: 99%